Xanthine Oxidase Inhibitors Screening, Antioxidation, and DNA Protection Properties of Geranium wilfordii Maxim. Issue 2 (23rd August 2019) - Liu, Yi; Mei, Shiyong; Xiao, Aiping; Liu, Liangliang
Abstract : Geranium wilfordii Maxim is a commonly used traditional medicine and as decoction pieces in drinks for treating acute and chronic rheumatalgia. Earlier research showed it could inhibit xanthine oxidase and had a strong antioxidative activity. In this study, four compounds namely, corilagin, geraniin, ellagic acid, and myricetrin were screened and identified as xanthine oxidase inhibitors and antioxidants using ultrafiltration combined liquid chromatography–mass spectrometry (LC–MS) and 1, 1‐diphenyl‐2‐picrylhydrazyl (DPPH) spiking combined LC–MS methods. Ellagic acid showed the greatest inhibition with IC50 of 0.018 ± 0.001 mM better than that of allopurinol. The kinetic parameters exhibited the mode of xanthine oxidase inhibitions by corilagin, geraniin, and myricetrin were the competitive types, whereas the ellagic acid was found as an uncompetitive inhibitor. In vitro DNA nicking assay showed these four compounds protected DNA from reactive oxygen species. Correlation analysis and partial least squares analysis showed there was a moderate correlation between ellagic acid and DPPH · scavenging activity. Our findings revealed four compounds in G. wilfordii Maxim contributed satisfied radicals scavenging, xanthine oxidase inhibition, and DNA damage protective activities. More comprehensive research on pharmaceutical applications and phytochemical profile of G. wilfordii Maxim could be further studied.